USE OF BACTERIAL LYSATES IN COMPLEX TREATMENT OF RHINOSINUSITIDIS - E.A. Vishneva; T.A. Polunina; L.V. Toropchina ("Paediatrician" Publishers LLC, 2011)
Rhinosinusitis is a common term that means inflammation of the mucosa of paranasal and nasal cavities. In the last 10 years there was a three-fold increase in rhinosinusitis' morbidity rates and annual increase of hospital admissions on the average of 1,5-2%. The prevalence of various forms of rhinosinusitidis among adult population is 5 to 15% and 5% among children. Such ubiquitous spreading is one of the leading factors that stipulate socio-economic burden of the disease. According to various studies, rhinosinusitidis dramatically decrease quality of life: these patients show more inferior results in tests upon pain sensitivity and social activity in comparison with patients with coronary heart disease and COPD; in approximately 26% of patients rhinosinusitidis are followed by development or progression of depression. Rhinosinusitis treatment is one of the hottest issues in modern otorhinolaryngology, that demand more financial support with every year. Achievments in immunology have become grounds for immunocorrection as part of complex treatment of such patients. Bacterial lysates are used as preventive medications.Key words: rhinosinusitidis, immunomodulators, bacterial lysates. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 157-161)